Upaya Peningkatan Pengetahuan tentang Penyakit Asma pada Masyarakat - Julia Putri; Lidia Naela Sangadah; Neng Wiwin Mulyati; Rini Fitriani (Yayasan Inspirasi El Burhani, 2022)
Introduction: Asthma is an inflammatory airway disease that can affect anyone, which is characterized by shortness of breath accompanied by a wheezing sound, but it varies from individual to individual, judging by the severity and frequency of this disease. predicts that in the future there will be an increase in the prevalence of asthma if it is not immediately prevented and handled properly. Objective: The aim of health education is to increase knowledge about prevention for asthma Method: The method used in this health education is direct health education (offline) and discussion. Result: The evaluation results show that the activities have been carried out properly following the indicators and results criteria on the observation sheet instrument. The observation sheet is based on five dimensions, namely timeliness and duration, participation, knowledge, job description, and problem-solving. The evaluation sheet is filled out by independent observers. Conclusion: By the evaluation results, health education activities to increase knowledge have been successful with individuals with indicators of timeliness and duration, participation, knowledge, job descriptions, and problem-solving. In the discussion session, all participants were enthusiastic to ask questions and listen and understand what the presenters answered from what they asked. In the post-implementation evaluation session, participants answered what was asked without hesitation. Observation results showed an increase in participant's knowledge. The pre-implementation evaluation showed that 1 out of 7 people gave responses to the questions given, could answer the questions correctly, but after the heath education, participants gave the correct feedback. This shows a change in the status of knowledge before and before health education is carried out. suggestions for this activity need time management so that counseling can be carried out according to the time specified in the SAP.